Time-Stable Wetting Effect of Plasma-Treated Biodegradable Scaffolds Covered with Graphene Oxide; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Marjin (Maryin) P. V. Pavel Vladimirovich; Rodriguez (Rodriges) Contreras R. D. Raul David; Bolbasov E. N. Evgeny Nikolaevich; Tverdokhlebov S. I. Sergei Ivanovich; Sheremet E. S. Evgeniya Sergeevna (Biomedical and Industrial Applications. Oral Presentation, 2019)
Заглавие с экрана